Pattern of Nutritional Intake among Obese Undergraduate in Faculty of Communication Studies Universitas Padjadjaran - Perianan, Nilavenmalar; Herawati, Dewi Marhaeni Diah; Wahyudi, Yudi (Althea Medical Journal, 2016)
Background: Obesity has become the 5th leading cause of death worldwide in 2010. It is a combination of genetic susceptibility, increased availability of high energy food intake and decreased requirements for physical activity in modern society. The increase in calorie intake among obese people often leads to many chronic diseases. Therefore, the aim of this study was to observe calorie intake pattern among obese undergraduates.Methods: This study was conducted at Faculty of Communication Studies Universitas Padjadjaran, from September to November 2013. This cross-sectional study used anthropometric measurement based on Asian Body Mass cut-off points, which the screening was conducted on 512 undergraduate students, consisting of 103 undergraduates, overweight (50) and obese (53). From 53 undergraduates, 30 respondents were randomly selected. The respondents were then interviewed using 3x24 hours Food Recall questionnaire, conducted on two weekdays and one weekend to observe their pattern of nutritional intake. Total number of calories was categorized into few groups according to the Recommended Dietary Allowance (RDA) 2012.Results: From the thirty obese undergraduates, both male (11) and female (9) consumed more excess protein in daily life. Consumption of carbohydrate and energy was significantly normal. Common consumption of food as daily basis contained more carbohydrate then protein, fats or energy.Conclusions: Prevalence of obesity is still high. Frequent meal and high intake of carbohydrates has become factors to nutritional imbalance of obese undergraduates. Types of food most widely consumed are white rice, fried chicken, tofu, tempe (asian food made from fermenting soybeans) and sweetened tea. [AMJ.2016;3(3):486â92]DOI: 10.15850/amj.v3n3.860